Kansas Beef Feedlot Managers' Trusted Sources of Information Concerning an Agroterrorism Event - Kendra Riley; Dwayne Cartmell; Traci Naile (Journal of Applied Communications, 2012)
Managers of Kansas beef feedlots were surveyed to determine managers’ preferred sources of information about agroterrorism as a foundation for law enforcement programs to disseminate information about protecting American animal agriculture. Developing producers’ awareness of and support for proposed law enforcement initiatives is vital to successfully implementing those strategies. Effective communication with producers depends on identification of producers’ preferred and trusted sources of information related to agrosecurity and agroterrorism. In this study, Kansas beef feedlot managers’ preferences for obtaining agrosecurity and agroterrorism information were described through a descriptive telephone survey. Feedlot managers’ preferences for veterinarians as sources of information were consistent with the results of previous studies and indicated the importance of veterinarians as channels for dissemination of information from law enforcement agencies. Managers’ preferences for veterinarians as a source of information also reflected behaviors associated with the persuasion stage of the innovation-decision process. Inclusion of veterinarians and other preferred sources of information in county Extension meetings and county Extension publications could add value to these channels for dissemination of agroterrorism information to Kansas beef feedlot managers. Feedlot managers’ adoption of agroterrorism preparedness programs may be enhanced by educational programs about preventive protocols.
Keywords: agroterrorism; feedlot; biosecurity; beef cattle; innovation; law enforcement; information sources